Effect of ageing on friction of human fingers - Kiyoshi Mabuchi; Rina Sakai; Kazuhiro Yoshida; Masanobu Ujihira (Biosurface and Biotribology, 2018)
Friction is an essential property of human fingers. Numerous studies have reported factors influencing finger friction. Friction on metal and plastic surfaces was measured because slipping of fingers could significantly affect industrial machine handling. By contrast, office workers may complain of fingers slipping on a paper surface, and lament that ageing reduces the friction of their fingers. The effect of ageing on finger friction against paper has not yet been studied. To clarify the effect of ageing, the authors measured finger friction on paper sheets, and discussed skin moisture as an important factor.